ANALISIS BEBAN KERJA, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL ADISURYA KEDIRI - Chriesna, Wanda Safira (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research was conducted at the Adisurya Hotel Kediri, where the hotel is one of the sectors needed to support tourism in the local area. The purpose of this study: 1) To analyze workload, compensation and job satisfaction have a significant partial effect on employee performance. 2) To analyze workload, compensation, and employee satisfaction have a significant simultaneous effect on employee performance. The method used is quantitative causality method. Data analysis techniques for this study: classical assumption test, multiple linear regression analysis, hypothesis testing (f test and t test) and coefficient of determination test. The results showed: 1) The results of the t-test of the workload variable had no significant positive effect on employee performance with a significance value of 0.140. 2) The results of the t-test of the compensation variable have a significant positive effect on employee performance with a significance value of 0.000. 3) The results of the t-test of the employee satisfaction variable have no significant positive effect on employee performance with a significance value of 0.558. 4) The results of the F test show that the variables of workload, compensation and employee performance have an effect on employee performance as indicated by the result of 0.000. 5) The results of the R2 test obtained results of 0.850. The important point in this study is that there is a positive but not significant effect on the workload and job satisfaction variables, so that it can be a new reference for future research.